Manajemen Pengetahuan dan Kinerja Terhadap Pengembangan Karir Karyawan: Studi SMA YBPK I Surabaya - Aprilia Andini; Alimatul Mukayah; Iriani Ismail (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: The purpose of this study is to examine how knowledge management and performance management affect the career development of employees at SMA YBPK I Surabaya.Methodology/approach: This study employs a qualitative descriptive methodology, gathering data from the Principal of SMA YBPK I Surabaya through structured interviews.Results/findings: Knowledge management and performance management, when used effectively, can enhance staff members' career development in the educational setting by raising their level of competence and drive for growth.Conclusions: Effective implementation of knowledge management can improve employee competence and adaptability, which in turn accelerates their career development. On the other hand, performance management helps evaluate and direct employees to achieve better targets through a regular evaluation systemLimitations: This research is limited to SMA YBPK I Surabaya, therefore the findings cannot be assumed universally applied to other schools. Moreover, data limitations could affect the analysis subjectively in order to provide a better understanding.Contribution: This research has the potential to enrich public understanding by providing valuable insights for all education stakeholders by highlighting the positive effect of knowledge and performance management combined.Keywords: Knowledge Management, Performance Management, Career DevelopmentHow to Cite: Andini, A., Mukayah, A., Ismail, I. (2025). Manajemen Pengetahuan dan Kinerja Terhadap Pengembangan Karir Karyawan: Studi SMA YBPK I Surabaya. Studi Ilmu Manajemen dan Organisasi, 6(1), 111-122.